Agronomic evaluation of herbaceous legumes in a subhumid zone of Uganda - Lusembo, P.; Mohamed-Saleem, M.A.; Tedla, A.; Sabiiti, E.N. (Informa UK Limited, 1995)
Sixteen promising forage legume accessions (15 species) were selected from small plot observation trials for agronomic evaluation over three years in a subhumid zone of Uganda. Macrotyloma axillare (Archer) significantly out yielded all other accessions in terms of annual dry matter production but not in terms of seed production. Stylosanthes guianensis ILCA 163, Clitoria ternatea and Centrosema pascuorum performed best for the tested attributes and were recommended for further agronomic and annual evaluation, albeit their introduction into Uganda is recent.